2006
DOI: 10.1093/jn/136.9.2384
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones Attenuate Human Monocyte Adhesion to Endothelial Cell–Specific CD54 by Inhibiting Monocyte CD11a

Abstract: Soy-based diets have been shown to protect against the development of atherosclerosis; however, the underlying mechanism(s) remain unknown. Interaction between activated monocytes and inflamed endothelial cells is an early event in atherogenesis. Therefore, we examined whether treatment of monocytes with soy phytochemicals could inhibit their adhesion to the endothelial cell-specific protein, CD54, a key factor in monocyte adhesion. Female Sprague-Dawley rats were fed AIN-93G diets containing soy protein isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Interestingly, soy-based diet inhibits the expression of MCP-1 in the aorta [22], and this observation is also supported by the reduced number of macrophages in atherosclerotic lesion in mice fed soy-based diets compared to control casein diet [22]. Moreover, coculture of human monocytes with endothelial cells resulted in the increased secretion of pro-inflammatory cytokines, such as IL-6 and IL-8, and the addition of soy isoflavones to the monocyte/endothelial cell co-culture inhibited the secretion of these pro-inflammatory cytokines [53]. However, plasma MCP-1 levels were not different in mice fed soy or control (casein) diet [22].…”
Section: Soy Diet Modulates Transmigration Of Monocytesmentioning
confidence: 80%
See 2 more Smart Citations
“…Interestingly, soy-based diet inhibits the expression of MCP-1 in the aorta [22], and this observation is also supported by the reduced number of macrophages in atherosclerotic lesion in mice fed soy-based diets compared to control casein diet [22]. Moreover, coculture of human monocytes with endothelial cells resulted in the increased secretion of pro-inflammatory cytokines, such as IL-6 and IL-8, and the addition of soy isoflavones to the monocyte/endothelial cell co-culture inhibited the secretion of these pro-inflammatory cytokines [53]. However, plasma MCP-1 levels were not different in mice fed soy or control (casein) diet [22].…”
Section: Soy Diet Modulates Transmigration Of Monocytesmentioning
confidence: 80%
“…Activation of monocytes and T lymphocytes results in the transformation of CD11a from a lowaffinity or avidity to a high-affinity or avidity form [56,57], and such a transformation leads to firm adhesion of inflammatory cells to vascular endothelium through CD11a-CD54 interaction. Recent in vitro studies have shown that pre-exposure of monocytes to soy isoflavones (1 μM) inhibited oxLDL-induced monocyte adhesion to endothelial cells [53]. However, this inhibition of monocyte adhesion is not due to the change in CD11a expression.…”
Section: Soy Isoflavone Regulates Monocyte Integrin Functionsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, milk and soy both contain estrogen-like components which may interact with estrogen receptors on monocytes and macrophages, influencing cellular responses (Purup, Vestergaard, Pederson, & Sejrsen 2006).The decrease in CD54 expression may prevent both monocyte stage and macrophage stage cells from adhering efficiently to endothelial cells (Maio & Del Vecchio 1992), impeding cell travel to the site of infection and therefore limiting the pro-inflammatory response. For soy treated cells, the soy isoflavone genistein may play a role in inhibiting monocyte adhesion (Nagarajan, Stewart, & Badger 2006) which could explain why even unfermented and acidified soy controls down-regulate CD54 expression to the same extent as that observed with soy ferments.…”
Section: Treatmentmentioning
confidence: 95%
“…Interactions between activated monocytes and inflamed endothelial cells are an early event in atherogenesis. Treatment of monocytes with soy phytochemicals inhibited their adhesion to the endothelial cell-specific protein, CD54, a key factor in monocyte adhesion [10].…”
Section: Introductionmentioning
confidence: 99%